Silver nanoparticles derived from Streptomyces sp. YJD18 with multifunctional biomedical applications - Lijuan Niu; Zihan Lin; Wenzhong Hu; Dongsheng Yang; Haitao Shen; Fei Guo (Scientific Reports)
Abstract A sustainable and energy-efficient approach was developed for the biosynthesis of silver nanoparticles (AgNPs) using a cell-free supernatant derived from Streptomyces sp. strain YJD18, an actinomycete isolated from saline soil. Optimized synthesis conditions, including pH 10 and a biomass concentration of 5 g/100 mL, facilitated the rapid formation of AgNPs. The highest yield was achieved by mixing the supernatant with silver nitrate (AgNO₃) at a 4:1 ratio, followed by incubation at 100 °C for 15 min.The synthesized AgNPs exhibited multifunctional bioactivities, including antibacterial, anticancer, antioxidant, and wound-healing properties, as confirmed by UV-Vis spectroscopy, transmission electron microscopy (TEM), X-ray diffraction (XRD), dynamic light scattering (DLS), high-angle annular dark field-scanning transmission electron microscopy (HAADF-STEM), Fourier-transform infrared spectroscopy (FTIR), and energy-dispersive X-ray spectroscopy (EDX). The formation of AgNPs was indicated by a characteristic color change, with UV-Vis spectral analysis revealing a distinct absorption peak at 420 nm. Morphological analysis showed that the nanoparticles were predominantly spherical, with a few triangular and cylindrical structures, measuring 50–80 nm in size, with a polydispersity index (PDI) of 0.312 and a zeta potential of -24.0 mV, indicating moderate colloidal stability. The AgNPs exhibited potent antibacterial activity against both Gram-positive (G⁺) and Gram-negative (G⁻) bacteria, with synergistic effects observed in combination with standard antibiotics. Furthermore, the AgNPs displayed significant anticancer activity, with pronounced cytotoxic effects against human pulmonary carcinoma (A549) and human liver hepatocellular carcinoma (HepG2) cell lines, compared to their effects on human breast adenocarcinoma (MDA-MB-231) and human cervical carcinoma (HeLa) cells.